BICONTINUOUS MICROEMULSION APPROACH TO DESIGN CONDUCTING COMPOSITE MATERIALS FOR ENERGY STORAGE - Yeszhan, Yelriza (School of Engineering and Digital Sciences, 2023)
In order to achieve good performance, it is important to control both the morphological and electrochemical characteristics of the electrode materials. In this regard, it is crucial to propose an appropriate synthesis technique. Among all conducting polymers, polyaniline attracts the most interest in the context of supercapacitors due to its ability to store energy via Faradaic processes. This study reports a new facile approach for the synthesis of PANI nanofibers, as well as 3D architectural polymers and their composites. Characterization methods such as Infrared Fourier transform (FT-IR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) Nitrogen adsorption has been used to study synthesized polyaniline-based materials. Furthermore, electrochemical approaches as electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and galvanostatic charge-discharge were applies to test performance of the polymer materials. According to the results of the study, the PANI nanofiber exhibits pseudocapacitive behavior with a capacitance value of 280 F g-1 at a current density of 1 A g-1 . Futhermore, the material shows an energy density of 14 W h g-1 and a maximum power density of 900 μm W g-1. Additionally, it should be noted that PANI retains about 98% of its original capacity after 1000 cycles. Thus, the PANI fiber electrode shows good cycling characteristics, suggesting the structural stability of the nanofibers. Even so, the PANI 3D supercapacitor has a low specific capacitance of 58.8 Fg-1 it was also stable and keep 98% of its capacitance after 637 cycles.
Keywords: type of access: open access; energy storage